2019
DOI: 10.3390/v11020092
|View full text |Cite
|
Sign up to set email alerts
|

Human Polyclonal Antibodies Produced from Transchromosomal Bovine Provides Prophylactic and Therapeutic Protections Against Zika Virus Infection in STAT2 KO Syrian Hamsters

Abstract: Zika virus (ZIKV) infection can cause severe congenital diseases, such as microcephaly, ocular defects and arthrogryposis in fetuses, and Guillain–Barré syndrome in adults. Efficacious therapeutic treatments for infected patients, as well as prophylactic treatments to prevent new infections are needed for combating ZIKV infection. Here, we report that ZIKV-specific human polyclonal antibodies (SAB-155), elicited in transchromosomal bovine (TcB), provide significant protection from infection by ZIKV in STAT2 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…These TcB's have limited long-term hyperimmunization, unlike vaccines, their adjuvants, or other immune stimulators. TcB's are currently used to produce fully human antibodies (polyclonal human IgG) against Hantavirus (HTNV) [ 65 , 66 ], Middle East Respiratory Syndrome coronavirus (MERS-CoV) [ 67 , 68 ], Ebola virus [ 69 ], Venezuelan equine encephalitis virus (VEEV) [ 70 ], Puumala virus (PUUV) [ 65 ] and Zika virus [ 71 , 72 ]. Recently, besides polyclonal antibodies, monoclonal antibodies have been produced in TcB against Influenza A Virus [ 73 ].…”
Section: Transchromosomic Bovines (Tcb's) Based Antibodiesmentioning
confidence: 99%
“…These TcB's have limited long-term hyperimmunization, unlike vaccines, their adjuvants, or other immune stimulators. TcB's are currently used to produce fully human antibodies (polyclonal human IgG) against Hantavirus (HTNV) [ 65 , 66 ], Middle East Respiratory Syndrome coronavirus (MERS-CoV) [ 67 , 68 ], Ebola virus [ 69 ], Venezuelan equine encephalitis virus (VEEV) [ 70 ], Puumala virus (PUUV) [ 65 ] and Zika virus [ 71 , 72 ]. Recently, besides polyclonal antibodies, monoclonal antibodies have been produced in TcB against Influenza A Virus [ 73 ].…”
Section: Transchromosomic Bovines (Tcb's) Based Antibodiesmentioning
confidence: 99%
“…CP was tested and showed efficacy (Table 2); however, HIG offered several advantages as a sustainable therapeutic option to provide a bridge between the outbreak and vaccine availability and to be administered upon infection to deliver immediate protection. Therefore, development of HIGs was evaluated 100,[130][131][132] for prophylaxis of ZIKV infection in at-risk populations, including women of childbearing potential and pregnant women. ZIKV-HIG, manufactured from human plasma with high titers of anti-ZIKV antibodies, was shown to prevent and/or neutralize ZIKV infection in preclinical studies using an immune-deficient mouse model (Ifnar1 -/-).…”
Section: Zika Virusmentioning
confidence: 99%
“…This study demonstrated an efficacy in vitro and in a mouse model of MERS-CoV infection showing how large quantities of human MERS-CoV-neutralizing antibodies can be rapidly produced in Tc bovines, providing a possible strategy for the development of passive immunotherapy against coronaviruses or other new and emerging infectious diseases 26 . Fully human polyclonal antibodies, produced in TcB, can be elicited against many viruses [26][27][28][29][30][31][32] (Ebola Zaire Virus) and some of them have already been shown to be safe and effective in human clinical trials 30,33 .…”
Section: Transchromosomic (Tc) Bovinesmentioning
confidence: 99%